Impact of Covid-19 on a European Stock Markets - Saraikin, Sergei (2023)
The aim of the work will be to analyze the impact of the Covid-19 pandemic on the European stock markets. The main hypothesis of this work is that the news and measures related to the COVID-19 pandemics have a strong impact on stock market returns. As a mythology for the analysis, the following data samples will be analyzed: the main stock indices for the country (eg the DАX index for Germany, the SMSI index for Spain, etc.) and the Cvid-19 cases. The collected data will be used in the test of significance (significance test) and the associated regression method Оrdinаry Leаst Squаres (ОLS) and the final t-tests also will be tested. Overall, it is expected that the impact on the stock market will be negative, but still controllable and influential.